Being Elder is Not Worst: Studi Tentang Proyeksi Pemuda Pada dan Saat Menjadi Lansia - Zuliani, Siti; Nuqul, Fathul Lubabin (Journal of Islamic and Contemporary Psychology, 2021)
The projection of becoming elderly is one of the things that young people rarely think about in facing the next phase. The purpose of this study was to analyze the projections of youth into the elderly, which include attitudes and readiness to care for the elderly, youth expectations when they become elderly, and the efforts made to face the elderly. The research involves 224 people, about 17-24 years of age. The gender distribution was 75 males and 149 females. Data collection using an open questionnaire. The analysis used is theme/categorization analysis and descriptive analysis. The results show that youth who care for the elderly are not necessarily ready to become elderly. Both prepared and unprepared, both groups of subjects hope to have a prosperous life, have financial independence, and have a happy family.